In search of the Holy Grail: a 20-year systematic review of the happy-productive worker thesis. Issue 5 (28th December 2020) - Sender, Gisela; Nobre, Gustavo Cattelan; Armagan, Sungu; Fleck, Denise
Abstract : Purpose: The relationship between job satisfaction and performance is a topic that has been intriguing scholars and managers for a long time. With the flourishing of positive psychology, it has been called the happy-productive worker thesis. New concepts led to new results but still divergent. This study aims to understand the past 20 years of research on the topic, also called the holy grail of the organizational sciences, helping to unwrap conclusions so far. Design/methodology/approach: Bibliometric analysis was performed with R statistical tool's support, complemented by content analysis, based on studies from three major databases between 1999 and 2019. The empirical studies were analyzed according to the constructs used, shedding light on when the happy-productive worker thesis is more likely to be confirmed. Findings: Results show a variety of constructs and instruments used to operationalize the constructs. This lack of convergence accounts for a large part of the general inconclusiveness of the topic. Indicated research gaps can be useful to both academics and practitioners. Research limitations/implications: Only studies declared as related to the happy-productive worker thesis were considered. Practical implications: Managers can benefit from considering the findings as a basis for decision-making regarding investments in employee happiness at work, focusing on the aspects of happy constructs that lead to productive criteria. Originality/value: The application of mixed methods, complementing the bibliometric with thorough content analysis, provided a more detailed overview of current knowledge about the topic, helping to disentangle different concepts that were treated as similar. Thus, it is possible to understand in which situations happy workers are really more productive.